PENGARUH PENDAPATAN, PENDIDIKAN, DAN GAYA HIDUP TERHADAP POLA KONSUMSI MASYARAKAT PELAKU USAHA - Mongkito, Abdul Wahid; Deshita, Salni; Sagiem, Zinnia Wahyunika (Robust: Research of Business and Economics Studies, 2024)
This research aims to find out how much influence income, education and lifestyle have on the consumption patterns of the business community in Konda Satu Village, Konda District, South Konawe Regency. This research uses quantitative methods with a population of 30 respondents and multiple linear regression analysis tools with the help of the SPSS program. The results of data processing show that partial income (X1) has a positive and significant effect on consumption patterns (Y), education (X2) has a positive and significant effect on consumption patterns (Y), and lifestyle (X3) has a positive and significant effect on consumption patterns (Y). In contrast, simultaneously income, education and lifestyle have a significant effect on consumption patterns.